Expression of Interleukin-1ß and Interleukin-8 in Oral Potentially Malignant Disorders and Carcinomas - Lopez-Labady, Jeaneth; Bologna-Molina, Ronell; Villarroel-Dorrego, Mariana (Frontiers in Oral Health, 2021)
Objective: To evaluate interleukin-1ß (IL-1ß) and interleukin-8 (IL-8) epithelial expressions in potentially malignant disorders of the oral mucosa as malignant predictive markers. Study design: About 55 tissues embedded in paraffin, comprising 15 oral lichen planus (OLP) lesions, 15 leukoplakias, 15 oral squamous cell carcinomas (OSCC), and 10 samples of normal oral mucosa were included in the study. IL-1ß and 8 expressions were assessed by immunohistochemistry using antibodies antihuman IL-1ß human (sc-7884, Santa Cruz® H-153) and antihuman IL-8 (ab7747, abcam®). The number of positive cells was compared using Student's t-test. Any p-value < 0.05 was considered statistically significant. Results: Nuclear and cytoplasmatic keratinocyte staining were positive for both cytokines in all study groups. However, a statistically significant decrease was observed within all cases compared to normal mucosa, both staining for IL-1β and 8. Moreover, IL-8 showed significant differences between OLP and leukoplakia, and when compared to OSCC. Conclusions: Oral epithelial expression of IL-1β and 8 seems to decrease when the malignant transformation of the oral mucosa increases.